Legume proteins as sustainable alternative proteins: composition, processing modifications, functional properties, and therapeutic potential in women’s health amid global protein shortage - Huijie Wu; Shaotao Jiang; Lewei Tu; Miao Dong; Lixian Wu; Yan Ai; Ying Liang; Ye Peng; Quancai Sun; Ying Xiao (Critical Reviews in Food Science and Nutrition, 2026)

Effects of oil body addition on the structure and oxidative stability of soybean oil-beeswax-based margarine - Lewei Ma; Yi Liao; Yukun Pei; Yu Gao; Jingwen Xu; Baokun Qi; Shizhang Yan; Lianzhou Jiang (Food Chemistry, 2026)

Measurement and Analysis of Influencing Factors of Green Total Factor Productivity in Mariculture: Empirical Evidence from China - Lewei Peng; Ying Ma; Linhua Peng; Zhoufu Yan; Lixia Zhang (Fishes, 2026)
Enhancing mariculture’s green total factor productivity (GTFP) is essential to balance industrial growth with ecology, safeguard global food security, and meet UN Sustainable Development Goal 14 amid mounting marine stress. As a global leading mariculture producer, China provides a typical research sample. This study constructs a mariculture GTFP measurement index system, estimates GTFP in China’s coastal provinces via the global Super-SBM model, identifies root causes of efficiency loss, and explores influencing factors and spatial spillover effects using a spatial econometric model. The results show that the overall mariculture GTFP of China’s coastal provinces exhibits a fluctuating upward trend with significant regional heterogeneity, specifically presenting a distribution pattern of “the highest in the South China Sea Region, followed by the East China Sea Region, and the lowest in the Yellow Sea and Bohai Sea Region”. Meanwhile, mariculture GTFP shows significant positive spatial autocorrelation, with distinct High-High and Low-Low agglomeration characteristics. Excessive resource consumption and undesirable output discharge are the core drivers of efficiency loss. For direct effects, industrial scale, industrial structure, fishermen’s income, transportation accessibility, internet development, technology adoption, and environmental regulation significantly boost local GTFP, while fishery disasters exert a significant negative impact. For spatial spillovers, industrial scale, industrial structure, and internet development show significant positive effects, while fishermen’s income and urbanization present negative effects. Based on these findings, this study proposes targeted multi-stakeholder optimization paths, providing decision support for China’s mariculture green development and replicable experience for global coastal countries.

Low-velocity impact response of bio-inspired multi-sinusoidal corrugated sandwich structure - Jing Sun; Honghui Li; Haikun Peng; Chao Ding; Lewei Yan; Xinmei Xiang (Engineering Structures, 2026)

Effect of different enzyme pretreatment on the structure and stability of soybean oil body - Yu Gao; Yi Liao; Yukun Pei; Lewei Ma; Baokun Qi; Shizhang Yan; Lianzhou Jiang (Food Chemistry, 2026)

Characterization of the soybean oil body interface: Revealing the mechanism of changes in the interfacial protein composition, structure, and function of oil bodies extracted under different denaturation conditions - Yi Liao; Yu Gao; Yukun Pei; Lewei Ma; Shizhang Yan; Baokun Qi; Yang Li (Food Hydrocolloids, 2025)

Single-Neuron Reconstruction of the Macaque Primary Motor Cortex Reveals the Diversity of Neuronal Morphology - Siyu Li; Yan Shen; Yefei Chen; Zexuan Hong; Lewei Zhang; Lufeng Ding; Chao-Yu Yang; Xiaoyang Qi; Quqing Shen; Yanyang Xiao; Pak-Ming Lau; Zhonghua Lu; et al. (Neuroscience Bulletin, 2025)

High emission of black carbon in heavy-duty diesel vehicles: Insights from microscopic operating conditions - Ting Chen; Xiao He; Liqiang He; Yan You; Lewei Zeng; Mingqiu Gao; Fengbin Wang; Yihuan Cao; Zhenhua Li; Xuan Zheng; Shaojun Zhang; Guangyi Xu; et al. (Science of The Total Environment, 2024)

Characterization of on-road nitrogen oxides and black carbon emissions from high emitters of heavy-duty diesel vehicles in China - Lewei Zeng; Shupei Xiao; Yifei Dai; Ting Chen; Hui Wang; Pan Yang; Guancong Huang; Min Yan; Yan You; Xuan Zheng; Shaojun Zhang; Ye Wu (Journal of Hazardous Materials, 2024)

The burgeoning importance of PIWI-interacting RNAs in cancer progression - Xinpei Deng; Tianle Liao; Jindong Xie; Da Kang; Yiwei He; Yuying Sun; Zhangling Wang; Yongluo Jiang; Xuan Miao; Yixuan Yan; Hailin Tang; Lewei Zhu; et al. (Science China Life Sciences, 2024)

Numerical and theoretical analysis of normal stress distribution in flanges of I-girders with trapezoidal corrugated webs under uniform bending - Guoji Zuo; Lewei Tong; Zhenbei Zhao; Hailin Wang; Chunyu Pan; Yan Li (Engineering Structures, 2023)

PP2Ac upregulates PI3K-Akt signaling and induces hepatocyte apoptosis in liver donor after brain death - Yan Xiong; Jianan Lan; Kaixin Huang; Yaruo Zhang; Lewei Zheng; Yanfeng Wang; Qifa Ye (Apoptosis, 2019)
Multiple research groups have demonstrated that the outcome of patients receiving liver grafts from brain death donors (DBD) is poorer when compared with patients receiving grafts from living donors. This might be due to an increased hepatocyte apoptosis induced after brain death (BD). In this work, we found that the activity of PP2A-Akt pathway is significantly increased in clinical donor ex vivo hepatocytes after BD by iTRAQ protein quantification analysis. The same results were confirmed in animal models. A time-dependent promotion of apoptosis was also found in DBD rabbit liver, as demonstrated by the increased levels of cleaved Caspase 3 and the decreased of Bcl-2. To further investigate the roles of PP2A and Akt in regulating apoptosis of hepatocytes after BD, we cultivated human liver cell line L02 with serum deprivation and hypoxia, to simulate the ischemic and hypoxic conditions of hepatocytes in DBD. Increased apoptosis and decreased viability were observed during the time in this model. Meanwhile PP2A activity and Akt activity were respectively increased and decreased. Notably, the proportion of Akt phosphorylation at Ser473 decreased, while other known targets of PP2A (p38, JNK and ERK) were not affected in terms of protein levels or phosphorylation. These results suggested that PP2A is involved in apoptotic induction of hepatocytes after brain death by specific suppression of Akt. This discovery was further confirmed with pharmaceutical and genetic methods. Our work implied potential targets for reducing liver cell apoptosis and improving organ donor quality after BD.